MODELLING OF THERMAL EXCHANGE IN AN ENCLOSURE (Sciences & Technologie. B, Sciences de l'ingénieur, 2005)
Our study concerns the modelling of the thermal exchanges by convection in an enclosure. We describe the experimental method used based on fluxes and heat exchange phenomena. The effect of the walls temperature on the thermal equilibrium of the cavity is shown. These exchanges taking place between vertical faces are generated by the flow. We will show that, in order to define these mean convection exchanges, the characteristic temperature difference must absolutely take into consideration the mean air temperature in the centre of cavities. We will give relations permitting to determine accurately this temperature after having determined the mean surface temperature for the six walls of the cavity. We will show the phenomenon of stratification and corresponding slope.